Implementing an Environment-based Curriculum at Madrasah Ibtidaiyah During the Covid-19 Pandemic - Nur Atikoh; Tati Nur Hayati; Ummi Nur Rokhmah (Al Ibtida: Jurnal Pendidikan Guru MI, 2022)
AbstractThe environment-based curriculum has not been simultaneously conceptualized and has not been optimally integrated into learning activities in Madrasah Ibtidaiyah (Islamic elementary school). Furthermore, the Madrasah environment as a learning resource has not been fully utilized. Therefore, the purpose of this research was to find out how an environment-based curriculum was applied during the Covid-19 pandemic and to describe the strengthening of character values in Madrasah Ibtidaiyah. This research was conducted at Madrasah Ibtidaiyah Darul Ulum, Cirebon City, West Java. Observation, interviews, and documentation were employed to collect data. The collected data were then analyzed by data reduction, data presentation, and data verification. The data analysis was interactive and triangulation was used to ensure data validity. The results showed that the implementation of the environment-based curriculum at Madrasah Ibtidaiyah Darul Ulum during the Covid-19 pandemic was integrated into subjects through activities such as house-waste recycling, land management and tree planting at home, energy-saving habits, and plastic-use reduction at home. The results suggest that teachers instill environmental awareness from an early age and use the environment as a learning tool.Keywords: curriculum implementation, environment, Covid-19 pandemic.Â AbstrakKonseptualisasi kurikulum berbasis lingkungan hidup belum diketahui secara simultan dan belum terealisasikan secara optimal dalam kegiatan pembelajaran di Madrasah Ibtidaiyah. Lingkungan Madrasah sebagai sumber belajar juga belum dimanfaatkan secara maksimal. Oleh karena itu, tujuan dari penelitian ini adalah untuk mengetahui bagaimana kurikulum berbasis lingkungan hidup diterapkan selama masa pandemi Covid-19 dan mendeskripsikan penguatan nilai-nilai karakter di Madrasah Ibtidaiyah. Penelitian ini dilaksanakan di Madrasah Ibtidaiyah Darul Ulum Kota Cirebon, Jawa Barat. Observasi, wawancara, dan dokumentasi digunakan untuk mengumpulkan data. Data yang terkumpul kemudian dianalisis dengan reduksi data, penyajian data, dan verifikasi data. Analisis keabsahan data menggunakan triangulasi data. Hasil penelitian menunjukkan bahwa implementasi kurikulum berbasis lingkungan hidup di Madrasah Ibtidaiyah Darul Ulum selama masa pandemi Covid-19 diintegrasikan ke dalam mata pelajaran, kegiatan pemanfaatan sampah di rumah, pengelolaan lahan dan penanaman pohon di rumah, kebiasaan hemat energi dan mengurangi penggunaan plastik di rumah. Hasil penelitian menyarankan agar guru dapat menanamkan kepedulian lingkungan sejak dini dan memanfaatkan lingkungan sebagai sarana belajar.Kata kunci: implementasi kurikulum, lingkungan hidup, pandemi Covid-19.